Aspergillus Tereus treated rice straw suppresses methane production and enhances feed digestibility in goats - P. Mohd Azlan; M. F. Jahromi; M. O. Ariff; M. Ebrahimi; Candyrine Su Chui Len; JB Liang (Springer, 2017)
The objectives of this study were to test the efficacy of producing lovastatin in rice straw treated with Aspergillus Tereus in larger laboratory scale following the procedure previously reported and to investigate the effectiveness of the treated rice straw containing lovastatin on methane mitigation in goats. The concentration of lovastatin in the treated rice straw was 0.69 ± 0.05 g/kg dry matter (DM) rice straw. Our results showed that supplementation of lovastatin at 4.14 mg/kg BW reduced methane production by 32% while improving the DM digestibility by 13% (P < 0.05) in goats fed fermented rice straw compared to those fed untreated rice straw. Populations of total methanogens and Metha no bacterial species were significantly reduced (P < 0.05) while the population of total bacteria and Ruminococcin albus were increased in the treatment group (P < 0.05). Our results demonstrated that lovastatin in the treated rice straw acted specifically on the methanogens by inhibiting the activity of HMG-CoA reductase in the methanogens’ cell membrane biosynthesis pathway and thus the growth of rumen methanogens as previously reported. This study provides a simple yet practical approach to mitigate enteric methane production particularly in the developing countries which depend heavily on the use of agro-biomass such as rice straw to feed their ruminant animals.